1989
DOI: 10.1111/j.1365-2133.1989.tb04175.x
|View full text |Cite
|
Sign up to set email alerts
|

An unusual case of trimethylaminuria

Abstract: A case is reported of trimethylaminuria that first developed in adulthood without any apparent cause. The patient developed a characteristic fish odour of his sweat, urine and to his breath after the consumption of choline-rich foods. Elevated levels of trimethylamine were present in the urine after dietary tests and identified by means of gas chromatography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…FMO3 is a major form of the enzyme present in adult human liver, where it plays an important role in the metabolism of trimethylamine (TMA). TMA is derived in vivo primarily from bacterial degradation of dietary choline, carnitine, and lecithin [2][3][4] which are found in foods such as egg yolk, liver, kidney, legumes, soybeans, peas, shellfish, and salt-water fish [4]. TMA is thought to be the primary endogenous substrate for FMO3, although it is possible that other biogenic amines such as tyramine [5] and phenylethylamine [6] may also be physiologically relevant substrates.…”
Section: Introductionmentioning
confidence: 99%
“…FMO3 is a major form of the enzyme present in adult human liver, where it plays an important role in the metabolism of trimethylamine (TMA). TMA is derived in vivo primarily from bacterial degradation of dietary choline, carnitine, and lecithin [2][3][4] which are found in foods such as egg yolk, liver, kidney, legumes, soybeans, peas, shellfish, and salt-water fish [4]. TMA is thought to be the primary endogenous substrate for FMO3, although it is possible that other biogenic amines such as tyramine [5] and phenylethylamine [6] may also be physiologically relevant substrates.…”
Section: Introductionmentioning
confidence: 99%
“…In these cases, there was neither familial nor personal history of the disorder, although common to all cases was the presence of previous or current liver pathology, such as hepatitis. It was therefore suggested that the acquisition of the disorder in these cases may be linked to insertion of viral DNA into the genome, which adversely affects the normal expression of the FMO3 gene 8 9…”
Section: Discussionmentioning
confidence: 99%
“…Whether the immunologic events associated with some forms of liver disease adversely affect FMO activity remains to be determined. Interestingly, one report describes a man developing fish-odour syndrome at 27 years of age, having had no previous history, and the authors suggested that this condition could be secondary to asymptomatic viral (A) hepatitis, as evidenced by the presence of serum antibodies (25). The overgrowth of intestinal microbes, Scand J Gastroenterol 1999 (5) associated with hepatic and kidney dysfunction, may also increase the liberation of trimethylamine from dietary precursors, leading to metabolic saturation.…”
Section: Discussionmentioning
confidence: 99%